Optimization and Validation of the Simultaneous Determination of Vildagliptin and Metformin, in Bulk and Formulation by A Reverse Phase HPLC Method Using D-Optimal Experimental Design - K Balamurugan; Kirtimaya Mishra (Journal of Global Pharma Technology, 2020)
This paper portrays a recently developed, optimized and validated isocratic RP-HPLC strategy for the separation of two anti-diabetic drugs Vildagliptin (VLD) and Metformin (MET).The optimization of the HPLC methodology included several variables, of which the impacts of each was studied. After a sequence of preliminary-screening experiments, the composition of the mobile phase and the pH of the added buffer solution were set as the examined variables, while the capacity factor (K1) of first peak i.e Metformin (MET), resolution (Rs) between Vildagliptin (VLD) and Metformin (MET), Separation (S) for both the drugs and the retention time (Rt2) of the second peak i.e Vildagliptin (VLD) were chosen as the dependent variables. Using the D-optimal design, the ideal chromatographic conditions for the separation were identified. The technique proved to show good harmony between the experimental data and predictive values throughout the studied parameter range. The optimum assay conditions were carried out with a Onyx C18 Monolithic column (100mm× i.d., 5µm) connected with an Onyx C18 guard cartridge (4mm×3mm i.d., 5µm) and a mixture of methanol (MeOH)/acetonitrile (ACN)/potassium dihydrogen orthophosphate (KH2PO4) (pH 4, 0.003 mol L−1) (31.362:10:58.638, v/v/v/v) as the mobile phase at a flow rate of 0.4 mL min−1 and detection wavelength of 220nm. The run time was under 8 min, which is a lot shorter than the prior optimized methods. The improved analytical method was validated as per FDA guidelines.